Development of the skills of critical thinking, creativity, innovation, and problem solving in Science ninth year, Costa Rica. (Revista Electrónica Calidad en la Educación Superior, 2021)
The present investigation was conducted during the second semester of 2018 and its purpose was to identify the development of the critical thought, creativity and innovation and problem resolution in the Sciences of the 9th year, Costa Rica, which should be addressed within other 10 more abilities, according to the proposal or curricular transformation by the Public Education Ministry. The paradigm used was naturalist with focus on the dominant qualitative and a phenomenological design, where three case studies related to everyday life were applied with the purpose of determining the development of the ability in the teaching and learning processes, the investigation subjects were 73 students from three different night schools in Heredia Educational Region. The information analysis was done by a pre-established rubric where the degree of ability development was determined. Among the main findings, it was discovered that the 3 abilities that were studied have a low development in the Science classes. Which indicates that the empowerment of these abilities has not been addressed in the classroom. Although this is required by the Science Study Program Circle III; therefore, it is fundamental that this be addressed in an integral manner with the docents through training in order to understand and internalize the importance of the pedagogical mediation in the classroom that increase the abilities applying the methodology using inquiries for Science.
Keywords: Skill; Critical Thinking; Creativity and Innovation; Problem Solving